PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KANTOR PERUSAHAAN DAERAH AIR MINUM KOTA PALU - Borman, Restutanti (Katalogis, 2015)
This research intends to explore and analyze : 1) the influence of transformational leadership style, motivation, and work environment on employees’ performance in PDAM office of Palu; 2) ) the influence of transformational leadership style on employees’ performance in PDAM office of Palu;3) the influence of motivation on employees’ performance in PDAM office of Palu; 4) the influence of work environment on employees’ performance in PDAM office of Palu. The sample consists of 35 employees from al units in PDAM office of Palu. The method of analysis is descriptive with multiple linear regressions. The results show that transformational leadership style, motivation, and work environment simultaneously affect employees’ performance with F-value of 24,967 on the sig. 0.000; transformational leadership style significantly affects employees’ performance with regression coefficient value of 0,376 on the sig. 0.001; motivation significantly affects employees’ performance with regression coefficient value of 0,401 on the sig. 0.000; work environment significantly affects employees’ performance with regression coefficient value of 0,166 on the sig. 0.023.